Abstract ID: 369 Dose tracking in diagnostic radiology: From implementation to operational tools. (December 2018) - Ghetti, C.
Abstract : Purpose: The recent introduction of dose tracking software has the potential to facilitate the collection of data and investigation of unusual high dose examinations. Furthermore, dosimetric data of radiological examination must be recorded and reported in order to face the request of the Euratom Directive 2013/59 [1]. We describe our experience with one of this software (Radimetrics version 2.5b, Bayer HealthCare [2]) that has been implemented to define local DRL for selected radiological examinations in Clinical Mammography and Computed Tomography, commonly considered crucial in terms of dosimetric impact. Methods: We have collected Average Glandular Dose (AGD) for 2 clinical mammographic units; CTDIvol, Size-Specific Dose Estimate (SSDE), Dose Length Product (DLP) and total DLP (DLPtot) for 5 CT scanners. Data have been compared with Italian Regulation and with the recent literature. The 75th percentiles of the different dosimetric indices have been calculated. Results: We have evaluated the 75th percentile of AGD for each radiogram on both mammography systems and the values are dosimetrically correct. The mean value of these results was defined as our local LDR. For exams performed with more than 5 acquisitions for breast, an alert message has been introduced in the Radimetrics system. Dosimetric data of the most common CT procedures performed on adult patients in our department have been analyzed. In most cases our values result lower or comparable with values reported in recent scientific literature and in Italian law. However, for some procedures we highlighted the need to reduce the number of scans in particular in CAP and chest-abdomen examinations performed on oncological patients. Conclusions: Automated methods of radiation dose data collection allow a fast and detailed analysis of a great amount of data and an easy determination of local DRLs for different radiological procedures.